ANALISIS FAKTOR KESADARAN LITERASI KEUANGAN SYARIAH MAHASISWA KEUANGAN DAN PERBAKAN SYARIAH - Nasution, Anriza Witi; Fatira, Marlya (EQUILIBRIUM, 2019)
This study aims to determine the factors that influence the financial literacy awareness of sharia financial and banking students in North Sumatra and also to find out the main factors that can influence that awareness. This study uses quantitative methods. The analytical tool used in this study is factor analysis. The subject of this research is students of Islamic finance and banking study programs in North Sumatra. The total sample of this study was 219 students using random sampling techniques. The results of the study indicate that there are four factors that influence the financial literacy awareness of students in Islamic finance and banking study programs in North Sumatra. The first factor is parents, the second factor is knowledge, the third factor is economic behavior, and the fourth factor is gender and information technology. While the main factors that can build financial literacy awareness of students in Islamic finance and sharia banking programs in North Sumatra are father's education, mother's education, and parents' income.